A non-destructive detection method for evaluating beef taste quality based on electrochemical PVC membrane sensor. (15th January 2022) - Wang, Xiaodan; Hu, Feng; Jin, Jiahui; Huang, Yue; Zhu, Xianming; Dong, Yanli; Wang, Cuilian; Wu, Duo
Abstract: A polyvinyl chloride (PVC) membrane sensor was developed to accurately detect beef taste quality grades. The beef taste was identified by the Fisher discriminant and verified by sensory evaluation. The PVC membrane sensor with the maximum open circuit potential (OCP) value and excellent performance was composed of 0.4 mL of dibutyl phthalate (DBP), 0.25 mL of lauryl ether phosphate, 3.6 mg of magnesium stearate and 6 mg of thermoplastic polyurethanes (TPU). Texture analyzer tests showed that the membranes showed desired physical properties, and the elasticity, viscosity and cohesion of the PVC membrane sensor were 4.74 mm, 2.17 mJ and 1.89 respectively. Scanning electron microscopy (SEM) showed the electrode immersed for 6 h without separation with PVC membrane. The coefficient of variation was less than 10% with a storage period of 7 months. Sensory evaluation showed that the beef sensory rated grades array determination by the Fisher discriminant method to verify the sensitivity of ammonia-sensitive substance-modified PVC membrane sensor had an accuracy of 93.3%. Highlights: Developed a new type of solid and corrosion resistant PVC membrane sensor. The data response of the PVC membrane sensor to measure beef taste is more pronounced and accurate. The accuracy of the new PVC membrane sensor for classifying beef is 94.4%. It is a nondestructive detection method for evaluating beef taste quality.